#Mulherespodcasters : uma análise da resistência feminista na podesfera brasileira - Silva, Alice dos Santos (2021)
Along with other media that developed on the internet, the podcast has gradually gained public and space in Brazil. In an essentially qualitative approach, despite considering quantitative data, this research has as main objective to understand what are the characteristics of feminist resistance built in the Brazilian podosphere by women podcasters. To achieve the results, I propose first a bibliometric and exploratory research considering the articles on podcast published in the Congresses of the Brazilian Society of Social Communication - Intercom. Based on these studies, it was possible to illuminate theoretical questions about the characteristics of the media, as well as to gather considerations about its functioning as a tool for disseminating content. For the empirical research, I carried out a survey of the most listened to programs in the country according to data from the 2018 PodPesquisa that had women on the team. As a tool for data collection, I applied semi-structured interviews with women producers of these programs who volunteered to participate in the study, and as a method, the Thematic Analysis proposed by Laurence Bardin (2011). 17 women who produced podcasts were interviewed, all of whom were cisgender women, mostly in their 30s. Almost 90% of the participants declared themselves to be white, and just over half are heterosexual. Only four respondents have children and 80% of them have completed higher education. Among the results found, it is noteworthy that even though they are not part of an organized collective, and having divergences from feminist conceptions, the women podcasters interviewed form a feminist activism concerned with making the podosphere a space of security and equality for women and other social minorities.